2020
DOI: 10.1080/20009666.2020.1807218
|View full text |Cite
|
Sign up to set email alerts
|

An internal medicine residency’s response to the COVID-19 crisis: caring for our residents while caring for our patients

Abstract: Background: In response to the COVID-19 pandemic, internal medicine residencies have had to develop new teaching strategies and attend to wellness concerns. Providing front-line care for patients in a time of widespread crisis while maintaining attention to training has created unprecedented challenges. Objective: Our large community hospital based internal medicine residency sought to develop and evaluate a crisis response to the demands of the COVID-19 pandemic to meet our residents' educational and wellness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Since the onset of the pandemic, support groups have been successful in promoting wellness for non-providers during the pandemic [21]. There are studies evaluating the impact of the pandemic response on wellness [22], but despite the negative impact of the pandemic on physician wellness, studies on wellness support initiatives during a pandemic are limited. One study found that a single support group session was very well received in supporting physicians through a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the pandemic, support groups have been successful in promoting wellness for non-providers during the pandemic [21]. There are studies evaluating the impact of the pandemic response on wellness [22], but despite the negative impact of the pandemic on physician wellness, studies on wellness support initiatives during a pandemic are limited. One study found that a single support group session was very well received in supporting physicians through a pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaei et al [ 21 ] have also reported stress, anxiety, the extension of training duration, and the reduction in the workforce due to COVID-19 in Iran. Detterline et al [ 22 ] reported the well-being needs of 88% of US residents were well met and that they were provided with effective communication (86%), scheduling/staffing (78%), preparation for clinical service (78%), and educational needs (76%). Rana et al [ 23 ] reported anxiety among residents in Brazil as a result of unknown professional future (84%).…”
Section: Discussionmentioning
confidence: 99%
“…Hospital and ICU beds were filled with patients, and many residents were reallocated from their scheduled rotations and ambulatory rotations to work in the emergency department, ward units, and ICUs given the increased need for medical personnel. 4,8,9,11 These reallocations may have been mandatory versus voluntary, but residents may have felt pressure to volunteer. 3 At one institution, half of the residents were reassigned with an additional quarter of residents on standby with the potential for reassignment.…”
Section: Stressorsmentioning
confidence: 99%
“… 11 Depending on the institution, either attendings or attending/resident teams were directly treating patients with COVID-19. 4,12 A proportion of residents had increased work hours, had greater odds of experiencing burnout, and may have been redeployed to patients outside their intended specialty. 9 …”
Section: Stressorsmentioning
confidence: 99%
See 1 more Smart Citation